Outcome, comorbidity, hospitalization and 30-day mortality after closure of acute perforations and postoperative anastomotic leaks by the over-the-scope clip (OTSC) in an unselected cohort of patients - Raithel, M.; Albrecht, H.; Scheppach, W.; Farnbacher, M.; Haupt, Werner; Hagel, Alexander; Schellerer, Vera; Vitali, Francesco; Neurath, Markus; Schneider, H. T. (Surgical Endoscopy, 2016)
Acute gastrointestinal (GI) wall defects contain a high risk of morbidity and mortality and may be closed endoscopically by a full-thickness over-the-scope clip (OTSC).Unselected consecutive patients presenting with acute non-surgical perforations or postoperative anastomotic leaks or perforations underwent attempted OTSC placement as primary closure method after interdisciplinary consensus in three tertiary referral centres. Their clinical data and intervention characteristics were evaluated in an intention to treat analysis during a 24-month period to assess closure rates, 30-day mortality, hospitalization and comorbidity.In total, 34 patients (16 females, 18 males, 69.5 years) were included with 22 non-surgical perforations and 12 postoperative anastomotic leaks or perforations. Definitive closure of the perforations and leaks was achieved in 26/34 patients (76.5 %). Successful closure of the GI wall defect resulted in a significantly shorter hospital stay (8 days, p = 0.03) and was significantly correlated with comorbidity (r = 0.56, p = 0.005). In the group with OTSC failure, hospitalization was 18 days and 6 of 8 patients (75 %) required immediate surgery. Three deaths occurred in the group with successful OTSC closure due to comorbidity, while one death in the OTSC failure group was related to a refractory perforation. Favourable indications and locations for a successful OTSC procedure were identified as PEG complications, endoscopic or postoperative leaks of stomach, colon or rectum, respectively.In unselected patients, OTSC was effective for closure of acute GI wall defects in more than 75 % of all patients. Clinical success and short hospitalization were best achieved in patients without comorbidity, but closure of the perforation or the anastomotic leak was found to be not the only parameter relevant for patient outcome and mortality.
EVALuna2:2224